HABITUS OF KHALAF ISLAMIC BOARDING SCHOOL AS A NATIONAL EDUCATION SUBSYSTEM (PPM MBS PRAMBANAN YOGYAKARTA CASE STUDY) - Agus Firmansyah; Sangkot Sirait; Ro’fah Ro’fah (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
This research is qualitative, with a case-study format. Data analysis is carried out by triangulating data. This research seeks to learn about the externalization and internalization of PPM MBS Yogyakarta's values, among other things. Second, explain the sentences and expressions that strengthen the habitus in PPM MBS Yogyakarta. The results of the study include: first, the habitus of the MBS pesantren was formed with three main components, namely Muhammadiyah ideology, government regulations, and the backgrounds of the core leaders and founders. Second, the habit is internalized by students through the integration of curriculum and habituation. For teachers, internalization is carried out with an initial commitment and weekly, monthly, and semi-annual studies